2022
DOI: 10.55493/5002.v13i1.4694
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark Beating and Earnings Manipulation in Nigerian Firms

Abstract: Earnings management among firms remains a central focus for academics, auditors and regulatory bodies. Benchmark-motivated earnings management occurs when managers engage in opportunistic activities, including flexible use of accounting standards to misrepresent the information in a firm’s financial reports. Academic research has focused on how firms manage earnings to beat benchmarks, but the evidence regarding firms in emerging African stock markets is scarce and none is available for Nigeria. We applied bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
1
0
1
Order By: Relevance
“…El‐Sayed Ebaid (2012) studied earnings management using the MBE threshold methodology in listed companies in Egypt and found that there were very few observations that appeared immediately below zero profits and very many observations that appeared immediately above zero profits, and this implied that many Egyptian listed firms engaged in earnings management to avoid reporting losses or earnings decrease. The findings by El‐Sayed Ebaid (2012) were not consistent with the findings by Gbadebo et al (2022) who studied earnings manipulation in Nigerian firms and employed the MBE technique. Their study involved 161 Nigerian listed firms from 2002 to 2019 and found there was no sufficient evidence associating change in earnings benchmarks with earnings discretions in the listed firms.…”
Section: Institutional Settingcontrasting
confidence: 79%
See 1 more Smart Citation
“…El‐Sayed Ebaid (2012) studied earnings management using the MBE threshold methodology in listed companies in Egypt and found that there were very few observations that appeared immediately below zero profits and very many observations that appeared immediately above zero profits, and this implied that many Egyptian listed firms engaged in earnings management to avoid reporting losses or earnings decrease. The findings by El‐Sayed Ebaid (2012) were not consistent with the findings by Gbadebo et al (2022) who studied earnings manipulation in Nigerian firms and employed the MBE technique. Their study involved 161 Nigerian listed firms from 2002 to 2019 and found there was no sufficient evidence associating change in earnings benchmarks with earnings discretions in the listed firms.…”
Section: Institutional Settingcontrasting
confidence: 79%
“…Their study involved 161 Nigerian listed firms from 2002 to 2019 and found there was no sufficient evidence associating change in earnings benchmarks with earnings discretions in the listed firms. TheGbadebo et al (2022) findings concurred with those ofPududu and Villiers (2016) studied earnings management through loss Avoidance or MBE method in South Africa and used 355 companies listed on the Johannesburg Stock Exchange (JSE) from 2003 to 2011 and found no evidence that managers of South Africa listed firms engage in earnings management by avoiding reporting small losses or small decreases in earnings. to the market value of a firm and that the link was even stronger with highquality sustainability disclosure.The past studies findings ofSmeuninx et al (2020),Nilipour et al (2020),Shuili and Yu (2020) andLoh et al (2017), agreed with the findings of…”
supporting
confidence: 70%